The Challenges of English Language Teaching in Indonesia - Roi Boy Jon; Rahimah Embong; Bambang Purnama; Ari Safar Wadi (ITScience (Information Technology and Science), 2021)
The widespread use of English worldwide has brought about a significant impact for human beings to date. In the education sphere mainly, many studies have been conducted to discover the issues in English instruction. Moreover, English teachers in Indonesia were highly encouraged to figure out the best method to teach and cope with any problems encountered by the students to achieve the best learning outcomes. Besides, the government had also tried its best endeavors to accustom the curriculum to the needs in this globalization era. However, the results have not always been as expected since teachers and students possessed divergent points of view linked with the implementation of English language instruction. Therefore, this scientific literature review discussed some issues related to English which included; English in Indonesia, English Language Teaching for Education, Teachers’ Strategies to English Language Teaching, Problems of English Language Teaching, and Students’ Perceptions towards English Language Teaching. Furthermore, the main aim of this paper was to acknowledge to the readers that the teachers and students essentially require English due to its crucial role in the development of Education in Indonesia.